Shining in Shadows : Movie Stars of the 2000s - Pomerance, Murray, 1946- (Book collections on Project MUSE., 2012)
Shining in Shadows examines a wide range of Hollywood icons from a turbulent decade for the film industry and for America itself. Perhaps reflecting our own cultural fragmentation and uncertainty, Hollywood's star personas sent mixed messages about Americans' identities and ideals. With a multigenerational, international cast of stars, this collection presents a fascinating composite portrait of Hollywood stardom today.